Time-saver standards for landscape architecture : design and construction data - Harris, Charles W.; Dines, Nicholas T. (New York: McGraw-Hill Book Company, 1988)
Time-Saver Standards for Landscape Architecture: Design and Construction Data is a book about building on the land, a comprehensive process which involves several elements: (1) interaction with existing natural and cultural systems, (2) dependence upon both site-specific and equipment-specific design and construction techniques, and (3) the use of a wide range of materials and devices...
Contributors -- Foreword -- Preface -- Acknowledgments -- Division 100: Processes -- Division 200: Standards and guidelines -- Division 300: Techniques -- Division 400: Structures -- Division 500: Improvements -- Division 600: Special Conditions -- Division 700: Site utilities -- Division 800: Materials -- Division 900: Details and devices.
Keywords: LANDSCAPE ARCHITECTURE; BUILDING; CONSTRUCTION INDUSTRY -- STANDARDS; LANDSCAPE ARCHITECTURE -- STANDARDS